Adsorption of Nitrate Ions onto Sepiolite and Surfactant-Modified Sepiolite - Adnan Özcan; Mutlu Şahin; Asiye Safa Özcan (Adsorption Science & Technology)
The adsorption of nitrate ions onto clay minerals has not been given much attention, possibly because clay surfaces are negatively charged. In order to increase the positive charge on the surface, sepiolite was modified in the present studies by treatment with dodecylethyldimethylammonium (DEDMA) bromide. After such modification, it was found that the maximum amount of nitrate ion adsorbed occurred at a pH value of 2.0. The chemical composition of natural sepiolite was determined by EDX methods and surface characterization of both natural and modified sepiolite samples was undertaken using FT-IR spectroscopic techniques. The adsorption of nitrate ions onto these adsorbents was determined by ion chromatography. The kinetic parameters of the adsorption process were calculated and it was shown that the reaction kinetic data could be fitted using the pseudo-second-order rate model. The calculated results indicate that both natural and surfactant-modified sepiolite are effective sorbents for the removal of anionic contaminants; however, the surfactant-modified sepiolite (453 mmol/kg) was more effective than the unmodified sepiolite (408 mmol/kg) in this respect. The adsorption data obtained were well described by the Freundlich adsorption isotherm.